“TRADIÇÃO E RENDA”: O TRABALHO INFANTIL NA FUMICULTURA NO MUNICÍPIO DE RIO AZUL, ESTADO DO PARANÁ NAS DÉCADAS DE 1950 A 2015 - Silva, Cleide Ferreira da (2016)
Child labor in tobacco growing in the municipality of Rio Azul is one of the most harmful forms of child and adolescent development and consequently for adults working in this form of production. The damage caused to people by the cultivation of tobacco since children are the most diverse that can affect their health, their school performance, their professional future and their quality of life. Child labor is not a specificity of Rio Azul, but the relationship with tobacco farming, the municipality's main agricultural product, makes it even more aggressive due to the widespread use of pesticides and excessive working hours. This dissertation seeks to analyze how the process of use of child labor occurred in the time cut from 1950 to 2010, how this process was started and the directions it has taken in the municipality since then. To reach this goal, we initially reconstructed the history of Rio Azul's economic development to understand when we started smoking, we discussed child labor in general and its implications for society and we discussed the uniqueness of this activity in the municipality. In this dissertation, documentary and oral sources were used, and interviews were conducted with six families of farmers from different locations in the city of Rio Azul: Taquari, Rio Azul dos Soares, Rio Azul de Cima and Marumbi dos Ribeiros. These localities were chosen because they are the ones that currently have the largest number of children and adolescents linked to child labor in the municipality.